Hierarchy of interfacial passivation in inverted perovskite solar cells. Issue 99 (28th November 2019) - Wang, Tun; Abbasi, Sadeq; Wang, Xin; Wang, Yangrunqian; Cheng, Zhendong; Wang, Jiayuan; Liu, Hong; Shen, Wenzhong
Abstract : The crucial hierarchy of the interfacial passivation at different positions of perovskite solar cells together with the corresponding mechanism has been studied despite the selection of passivation mediums in this work. Abstract : The crucial hierarchy of the interfacial passivation at different positions of perovskite solar cells together with the corresponding mechanism has been studied despite the selection of passivation mediums in this work. The passivation on the upper interface could more effectively enhance the device performance with an efficiency of 19.55% compared to the pristine and lower passivated cells (15.90% and 18.39%, respectively). Furthermore, the upper passivated devices exhibit better long-term and thermal stability than the lower passivated and pristine ones.